Dobór małżeński i integracja imigrantów w małżeństwach mieszanych - Stan badań - Anita Brzozowska (University of Warsaw, Centre of Migration Research (CMR), 2015)
– The aim of this study is to present the state of the art of research on mixed marriages in terms of ethnicity and nationality. The study covers the works on mate selection and immigrants integration. It begins with an overview of existing definitions of marriage and types of mixed marriage as well. These introductory reflections are followed by the presentation of marital matching process and social integration of immigrants from different theoretical perspectives. Then, the analysis of studies of intermarriage come in first place focusing primarily on migration studies. The study ends with the conclusions that summarize the most important scientific achievements of researchers in the field of intermarriage research. It encompasses also separate section on the potential of the intermarriage research in Poland.
Keywords: 330; mixed marriages; integration; migration; mate selection